Pharmacological Management of Chronic Neuropathic Pain: Revised Consensus Statement from the Canadian Pain Society - DE Moulin; A Boulanger; AJ Clark; H Clarke; T Dao; GA Finley; A Furlan; I Gilron; A Gordon; PK Morley-Forster; BJ Sessle; P Squire; et al. (Pain Research and Management)
BACKGROUND: Neuropathic pain (NeP), redefined as pain caused by a lesion or a disease of the somatosensory system, is a disabling condition that affects approximately two million Canadians.